Les attentes et le sexisme en counselling - Sicuro, Francesca; Lecomte, Conrad; Bernstein, Bianca (Canadian Journal of Counselling and Psychotherapy, 2012)
The primary objective of this study is to evaluate sexism in counselling as a function of counsellors' expectancies and client's and counsellor's sex differences. In an analogue study, 340 counsellors from Québec were asked to read a brief case history of a hypothetical client, and then to answer an inventory on expectancies. Results indicate that client sex influences the counsellor's expectancies with female clients revealing a more favorable diagnosis and prognosis. Moreover, results indicate that female counsellors have higher prognostic expectancies than male counsellors, while male counsellors have higher process expectancies. Results are discussed in terms of the importance of the role of client and therapist sex in the study of the therapeutic relationship.